Estudo de blenda polimérica PET/PE aplicado na reciclagem de aparas de filmes multicamadas - Uehara, Gabriel Abreu (Universidade Federal de São Carlos, 2013)
The main objective of this work was to analyze the viability of the recycling of post-industrial packaging scraps, compounded by multilayer laminated films of PET-HDPE, for production of polymer blends with good physical-mechanical performance. Initially, several PET-HDPE model-blends were developed utilizing pure resins, in which had similar characteristics to the polymers that are effectively utilized by the cosmetic industry that generate the scraps. The model-blends were produced in diverse formulations, starting from a 2² full factorial design of experiments (DOE) and expanding it afterwards to a central composite design, in which varied the PET/HDPE ratio from 0 to 100 wt%. Polyolefin compatibilizers based on glycidyl methacrylate (E-GMA) and maleic anhydride (PE-g-MA) have been used to promote the compatibilization reaction between PET and HDPE. The physical-mechanical properties of the model-blends were evaluated by means of response surface methodology (RSM), a scientific tool that provides a multivariate data analysis. Finally, the post-industrial plastic scraps were diluted in the same compatibilizer concentrations that defined the best conjunct of physical-mechanical properties for the model-blends. The DOE methodology showed to be a useful tool for assessing the recycling of post-industrial scraps, since it was possible to obtain recycled materials with considerable physical-mechanical properties. The deformation at yield enhanced with compatibilizers concentration, while the Young modulus diminished. The utilization of 10 wt% of PE-g-MA enhanced 12x the values of deformation at break, while the use of 10 wt% of E-GMA barely doubled the values of the property. Additionally, the blends compatibilized with PE-g-MA also showed a better performance under impact test. The utilization of 15 wt% of PE-g-MA enhanced the Izod impact resistance in 250%. The better performance of maleic anhydride based compatibilizer (PE-g-MA) is due to the possible presence of nylon-6 at the structure of the scraps, which undergoes a kinetically favorable chemical reaction, facilitating the compatibilization between the components. Finally, one could be demonstrated that starting from a technological premise it s possible to develop scientific models that optimize the recycling route of multilayer flexible packaging films that arise from cosmetic industry.
Keywords: Polímeros; Blendas poliméricas; Planejamento experimental; Compatibilização reativa; Reciclagem; Filmes multicamadas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA